(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Counseling is a relationship between thecounselor and the counselee wherein the latter is helped to gain better insightinto his/her problems, abilities and potentialities. The counselor createsconducive atmosphere where in the counselees talk about their problems openly.The counselor listens empathetically and helps them think independently andcreatively. This paper presents role of counseling in increasing progress rateof students.